Chapter Extravagancias textuales de una suelta de La fingida Arcadia, comedia de tres ingenios - Trambaioli, Marcella (Studi e saggi, 2021)
La fingida Arcadia's textual transmission, play of multiple authorship, includes a suelta conserved just in Bayerische Staatsbibliothek (S3), that corresponds to a text very far from the rest of the tradition. The suelta maintains unaltered the plot of the original play, even if it modifies all over the dialogues, cuts or lengthens whole fragments, intensifies the courtisan features and, most of all, elaborates especially the burlesque motive of the mondongas. At the same time, the author omits all those elements related to the practice of multiple authorship in order to proclaim, indirectly, to be the author of a different play, announced by the modified title.